Disability conceptions in adoptive parents and adoption applicants: the ableism as a barrier - de Oliveira, Taize [UNESP] (Universitat Autonoma de Barcelona, 2022)
The inclusion of people with disabilities still comes up against barriers, especially attitudinal barriers. The adoption of children with disabilities, in addition to being an action that ensures the fundamental right of family life, is ultimately one of the scenarios that seek inclusion and that still reveals ableist barriers. The present study aimed to identify conceptions of disabilities in four adoptive parents and four applicants for adoption, and to relate with motivators or not of the adoption of children with disabilities. The results indicated a strong tendency to agree with the biological conception of the deficiency associated with the idea of dependence of these children, related to ableism. The study identifies a lack of access to content about deficiencies during the adoption process, and indicates the possibility of the performance of technicians who can act in this process, informing, in forums and support groups for adoption.
Concepções de deficiência de pais adotivos e pretendentes à adoção: o capacitismo como dificultador
Keywords: Ableism; Adoption; Conceptions of Disability; Disabled Child